The human auditory system : fundamental organization and clinical disorders - Celesia, Gastone G.; Hickok, Gregory (Amsterdam, Netherlands : Elsevier B.V., 2015)
"The Human Auditory System: Fundamental Organization and Clinical Disorders provides a comprehensive and focused reference on the neuroscience of hearing and the associated neurological diagnosis and treatment of auditory disorders. This reference looks at this dynamic area of basic research, a multidisciplinary endeavor with contributions from neuroscience, clinical neurology, cognitive neuroscience, cognitive science communications disorders, and psychology, and its dramatic clinical application"--Publisher's description
Section 1: Anatomy and physiology of the human auditory system. Auditory pathways: anatomy and physiology / James O. Pickles -- Anatomical organization of the auditory cortex / Troy Hackett -- Development of the auditory system / Ruth Y. Litovsky -- Representation of loudness in the auditory cortex / Christoph Eberhard Schreiner -- Temporal coding in the auditory cortex / Anne-Lise Giraud -- Sound localization / John C. Middlebrooks -- Learning and plasticity in auditory cortex / Norman M. Weinberger -- Neural basis of speech perception / Gregory Hickok -- Role of the auditory system in speech production / Frank Guenther -- White matter pathways for auditory and speech processing / Angela Dorkas Friederici and Sarah Gierhan -- Neural basis of music perception / Petr Janata -- Music and language: relations and disconnections / Nina Kraus and Jessica Slater -- Section 2: Methodology and techniques. Invasive recordings in the human auditory cortex / Matthew A. Howard III and Kirill V. Nourski -- Electromagnetic recording of the auditory system / David Poeppel and Gregory Hickok -- Hemodynamic imaging of the auditory cortex / Deborah Hall -- Imaging white matter pathways / Marco Catani -- Electrophysiological auditory tests / Alan D. Legatt -- Psychophysical and behavioral peripheral and central auditory tests / Frank E. Musiek and Gail D. Chermak -- Section 3: Disorders of the auditory system. Neurocognitive development in congenitally deaf children / Elizabeth M. Fitzpatrick -- Aging of the auditory system / Thomas Nicolas Roth -- Decreased sound tolerance: hyperacusis, misophonia, diplacousis and polyacousis / Pawel J. Jastreboff -- Auditory synesthesias / Pegah Afra -- Tinnitus / Robert Aaron Levine -- Auditory hallucinations / Jan Dirk Blom -- Palinacousis / Madeline C. Fields -- Musicogenic epilepsy / John M. Stern -- Deafness in cochlear and auditory nerve disorders / Kathryn Hopkins -- Auditory neuropathy / Arnold Starr -- Hearing disorders in brain stem lesions / Gastone G. Celesia -- Central auditory processing disorders in children and adults / Teri James Bellis -- Auditory neglect and related disorders / Alexander Gutschalk and Andrew Dykstra -- Auditory agnosia / L Robert Slevc -- Congenital amusias / Barbara Tillmann, Philippe Albouy and Anne Caclin -- Acquired amusia / Jason D. Warren -- Hearing disorders in stroke / Doris-Eva Bamiou -- Hearing disorders in multiple sclerosis / Miriam Furst-Yust -- Hearing and music in dementia / Julene K. Johnson and Maggie L. Chow -- Future advances / Gastone G. Celesia and Gregory Hickok
Includes bibliographical references and index
Also issued online
1 13
Keywords: Auditory Cortex -- physiology; Auditory Pathways -- physiology; Auditory perception; Auditory perception; Hearing Disorders -- physiopathology; Hearing -- physiology